2022
DOI: 10.1016/j.jhepr.2021.100398
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immunity in hepatitis B virus infection: Rehabilitating the B in HBV

Abstract: Summary Insights into the immunopathogenesis of chronic HBV infections are fundamental in the quest for novel treatment approaches aimed at a functional cure. While much is known about the ineffective HBV-specific T-cell responses that characterise persistent HBV replication, B cells have been left largely understudied. However, an important role for humoral immunity during the natural history of HBV infections, as well as after functional cure, has been inadvertently revealed by the occurrence of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 123 publications
1
10
0
1
Order By: Relevance
“…There are 3 major guidelines that have prespecified stopping criteria to ensure patient safety after NA withdrawal; however, these tend to vary by geographical region and local reimbursement policies (6)(7)(8)(9). Because hepatitis B e antigen (HBeAg) seroconversion comes with increased immune control, the HBeAg status also plays an important role in assessing patient eligibility for treatment cessation (10).…”
Section: Introductionmentioning
confidence: 99%
“…There are 3 major guidelines that have prespecified stopping criteria to ensure patient safety after NA withdrawal; however, these tend to vary by geographical region and local reimbursement policies (6)(7)(8)(9). Because hepatitis B e antigen (HBeAg) seroconversion comes with increased immune control, the HBeAg status also plays an important role in assessing patient eligibility for treatment cessation (10).…”
Section: Introductionmentioning
confidence: 99%
“…When the liver becomes inflamed due to HBV infection, a large number of chemokines such as CXCL10 and CXCL11 are produced, which can increase during local viral infection and produce directional migration signals. They play a chemotactic role for various inflammatory cells in the circulation and cause them to selectively migrate to specific sites via vascular endothelial cells to exert an antiviral effect 2,28 . So that, the high expression of CXCL10 protein in liver tissue suggests a more effective antiviral effect, such as in the present study, where immunohistochemical results showed that CXCL10/CXCR3 protein levels in the liver were significantly higher than the protein levels of HBeAg patients with antiviral treatment after 96 weeks, but the change in CXCL10/CXCR3 had no significance in HBeAg non‐SC patients.…”
Section: Discussionmentioning
confidence: 44%
“…HBcAb is the earliest antibody produced after patients are infected with HBV, which is an important marker of hepatitis B infection. However, it is not a protective antibody [34]. Song et al [35] found that the quantitative serum levels of HBcAb in chronic HBV-infected patients were closely correlated with hepatitis activity.…”
Section: Discussionmentioning
confidence: 99%